2013
DOI: 10.1583/12-4057.1
|View full text |Cite
|
Sign up to set email alerts
|

Open Fenestration of the Distal Landing Zone via a Subxyphoid Incision for Subsequent Endovascular Repair of a Dissecting Thoracic Aneurysm

Abstract: In this case of chronic dTAA, open surgical removal of a segment of the dissection flap via a subxyphoid incision provided a distal landing zone for subsequent endoluminal repair, with exclusion of the aneurysm and preservation of antegrade flow in both true and false lumens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…This smart strategy sought to facilitate complete distal seal of the thoracic false lumen aneurysm by landing a thoracic stent-graft during a second procedure in this combined lumen. Konings et al 12 reported a similar approach via a subxiphoid incision and resection of the dissection membrane in the supraceliac aorta, extending Roselli's technique even further distal without the need for thoracotomy or sternotomy in a patient with a chronic aortic dissection type B. Both strategies address the problem of false lumen backflow sufficiently, but require open surgery and aortic cross-clamping.…”
Section: Discussionmentioning
confidence: 99%
“…This smart strategy sought to facilitate complete distal seal of the thoracic false lumen aneurysm by landing a thoracic stent-graft during a second procedure in this combined lumen. Konings et al 12 reported a similar approach via a subxiphoid incision and resection of the dissection membrane in the supraceliac aorta, extending Roselli's technique even further distal without the need for thoracotomy or sternotomy in a patient with a chronic aortic dissection type B. Both strategies address the problem of false lumen backflow sufficiently, but require open surgery and aortic cross-clamping.…”
Section: Discussionmentioning
confidence: 99%
“…However, visceral debranching with extended distal aorta coverage is associated with significant morbidity and mortality, and not all patients are amenable to branched and fenestrated endografting [9,15,17,18]. Fenestration techniques, such as open fenestration or the knickerbocker technique, create a single lumen surgically or percutaneously to allow the stent graft to seal the FL aneurysm distally [16,19,20]. This method requires an open approach or anatomic suitability.…”
Section: Commentmentioning
confidence: 99%
“…The surgical morbidity is probably reduced by avoiding a thoracotomy or thoracoabdominal incision. After our initial report, other groups have also adopted this strategy and reported a few cases with open or endovascular fenestration to create adequate distal landing zones for subsequent endovascular repair [22,23]. Based on the principles demonstrated during this surgical experience, we have also been using a balloon fracture fenestration technique to optimize stent graft expansion and promote earlier remodeling by creating a distal landing zone after ballooning.…”
Section: Secondary Delayed Aortic Interventionsmentioning
confidence: 99%